(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
Labor migration is a situation that arises on the verge of a crisis in the local labor market. The International Labor Organization identifies the following main types of labor migration: contract labor, migration of skilled labor and illegal migration. It should also be borne in mind that there are significant problems in the analysis of migration processes. In particular, in most cases migrants are exploited and their rights violated. The increase in the international mobility of intellectual labor resources in the country is also due to the fact that migration is poorly regulated.